(untitled) (Scientific journal of the Fergana State University, 2024)
This article highlights the importance of political PR in communicative processes, controlling individuals, and election campaigns. One of the most important functions of PR technologies and mass media communications is the analysis of the role of the political culture in the modernization of society. Also, it is based on examples of the media’s role in the social and political life of the society.